Problems of forming of ecological conception of community development - Olena Rudneva (Cхід, 2013)
Ukraine's ecologico-economical strategy on the way towards creating a new system of environmental safety regulation is based on development of instruments that will provide changes responding to the events already happened to the system and taking effective nature protection projects to prevent pollution natural environment. An important direction to prevent technogenic accidents and catastrophes is the realization of aims of State Environmental Policy: providing of principles of sustainable development, toughening of norms of nature protection legislation, analysis and prognostication of environmental threats, realization "Polluter-User-Pays-Principle for all in price", environmental involvement of all interested parties. In the article the necessity of forming of the renewed ecological conception of community development is grounded. The evolution and features of ecological consciousness of people is studied. An environment for a people is a method of satisfaction of material necessities; subject-object perception of nature; pragmatic character of reasons and aims of interrelation with an environment. Recommendations on formation new relations in the system "society - natural environment" are proposed. It is necessary to perfect not only the economical and administrative-legel instruments of society's influence on an natural environment but also to enhance significancy of socialpsychological regulators.